Chinese E-consumer satisfaction: Insights from the online travel agency sector - Sun, Lei; Chamsuk, Wawmayura; Saengnoree, Amnuay; Sornsaruht, Puris (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the key factors influencing e-consumer satisfaction (E-SAT) within China's online travel agency (OTA) industry. Specifically, it explores the impact of consumer value (CV), service innovation (SI), and brand image (BI) on user satisfaction, providing insights for enhancing competitive advantage in the digital travel ecosystem. A quantitative research design was employed using a structured questionnaire distributed to 361 Chinese OTA users. The instrument demonstrated high reliability (Cronbach's alpha ranging from 0.86 to 0.88). SPSS Version 24 was used to conduct a Pearson correlation analysis and to examine relationships among the variables CV, SI, BI, and E-SAT. The results revealed that all three predictors—CV, SI, and OTA BI—were significantly and positively correlated with E-SAT. Notably, consumer value exhibited the strongest correlation (r = 0.92, p < 0.01), followed by service innovation (r = 0.89, p < 0.01) and brand image (r = 0.87, p < 0.01). These findings underscore the strategic importance of delivering value-driven, innovative, and brand-aligned digital experiences in the OTA sector. The study confirms the critical role of consumer value and innovation in shaping consumer satisfaction in OTAs. OTAs can drive sustained user engagement and loyalty by aligning platform design and service delivery with user expectations. Integrating CV and SI into consumer experience strategies offers a pathway toward sustainable digital competitiveness. This research provides actionable insights for OTA managers, developers, and marketers aiming to improve consumer satisfaction. Emphasizing consumer value creation, continuous innovation, and coherent brand messaging can enhance user trust and platform loyalty. The study contributes to the broader e-service quality and consumer experience management field in emerging digital travel markets.